The pueblo decomposition model: A method for quantifying architectural rubble to estimate population size. (January 2016) - Duwe, Samuel; Eiselt, B. Sunday; Darling, J. Andrew; Willis, Mark D.; Walker, Chester
Abstract: While most archaeological measures of population rely on material proxies uncovered through excavation (rooms, hearths, etc.), we identify a technique to estimate population at unexcavated sites (the majority of the archaeological record). Our case study focuses on ancestral Tewa Pueblo villages in northern New Mexico. Uninhabited aerial vehicle (UAV) and instrument mapping enables us to quantify the volume of adobe architectural rubble and to construct a decomposition model that estimates numbers of rooms and roofed over space. The resulting metric is applied at ten Pueblo villages in the region to 'rebuild' architecture, and calculate maximum architectural capacity and the maximum extent of population size. While our focus is on population histories for large Classic period (A.D. 1350–1598) pueblos in the American Southwest, the model and method may be applied to a variety of archaeological contexts worldwide and is not limited to building material, site size, or construction technique. Graphical abstract: Highlights: Paper addresses how to empirically estimate site population from unexcavated contexts. Architectural rubble volume proposed as a proxy for estimating population size. Aerial and instrument mapping of mound volume at 10 Tewa Pueblo sites in New Mexico. Model extrapolates living space and maximum architectural capacity from rubble volume. Model is globally applicable and not limited to material or construction type.